Home: The Interplay Between Text and Photograph - Qiu, Yi (Auckland University of Technology, 2016)
This project examines the interplay between text and photograph. It explores how photography can be affected by any text contained within the photograph. Both photograph and text are tools that can be read to construct meaning. “Photographs, which cannot themselves explain anything, are inexhaustible invitations to deduction, speculation, and fantasy” (Sontag, 1977, p. 22). In this research, the potential to construct multiple meanings allows photograph the possibility of cooperating with and being altered by the chosen text. Choosing a particular text may effectively lead the audience to a “more precise understanding of a given subject” (Havermans, Keegan, Har- tog, 2015). The meaning of the object (text and photograph), can be “swept from one sphere into another” (Norridge, 2009). The relationship between text and photograph is a complex two-way interaction, in which even subtle changes can potentially transform the nature of how they cooperate with each other. Contextually, the research re ect on the Asian gay community as the context in my research, and its identity in New Zealand through daily life activities of the participants. This project will also ap- proach, explore and recognise both the original resolution of the notion of home (HOME), the Asian gay community (HOMO) and the identity (ME).
Keywords: Interplay; Text; Photograph; Gay; Asian; Home